Digital Transformation of Small Medium Enterprises: A Descriptive Analysis of Quick Response Indonesia Standard Data - Arianto Muditomo; Novita Setyawati (Jambura Equilibrium Journal, 2022)
The purpose of this study is to explain the digital transformation of Indonesian micro and medium enterprises (SMEs) through descriptive data analysis on the implementation of the Indonesian quick response standard (QRIS) through the end of 2021. The implementation of QRIS in Indonesia increases literacy and electronic financial inclusion among Indonesian SMEs, attempting to make it easier for the government to conduct better monitoring of SME transactions. The development of QRIS, which began in 2019, has proven to be capable of improving the documentation of digital financial inclusion of SMEs with 14.78 million merchants, the majority of whom are SME merchants, specifically micro business merchants (UMI), small business merchants (UKE), and medium business merchants (UME). Similarly, SMEs dominate in terms of volume and nominal transactions. This descriptive analysis will provide an overview of the evolution of SME digitization in Indonesia, which market players and regulators can use to develop policies and strategies for the future of SMEs.